GlyT1 inhibition by ALX-5407 attenuates allograft rejection through suppression of Th1 cell differentiation - Zhang, Xiaohan; Zhang, Weiqi; Wei, Jianghao; Jin, Shuai; Wang, Zhen; Wang, Hui; Feng, Gang; Zhao, Jie (Frontiers in Immunology, 2025)
ObjectiveTransplant rejection driven by Th1 cell-mediated immune responses remains a critical challenge. This study aimed to investigate the role of glycine transporter 1 (GlyT1/SLC6A9) in Th1 differentiation and evaluate the therapeutic potential of its inhibitor, ALX-5407, in attenuating allograft rejection.MethodsRNA sequencing, flow cytometry, and qRT-PCR were employed to analyze GlyT1 expression in Th1-polarized CD4+T cells. ALX-5407 (0.5–500 nM) was tested in vitro under Th1-polarizing conditions. A murine skin allograft model (BALB/c to C57BL/6) was established to assess graft survival and immune responses. Combination therapy with rapamycin and ALX-5407 was evaluated through histopathology, immunofluorescence, and splenocyte profiling. Mechanistic insights were derived from RNA-seq, KEGG/GO enrichment, and Western blotting.ResultsGlyT1 expression was significantly upregulated in Th1 cells and rejection cohorts. ALX-5407 suppressed Th1 differentiation, reducing IFN-γ+CD4+T cells proportions (p < 0.05) and activation markers (CD25, CD69), while inducing apoptosis via caspase-3 activation and BCL-2 downregulation. Although ALX-5407 monotherapy failed to prolong graft survival, combination with rapamycin synergistically enhanced efficacy (p = 0.018), reduced inflammatory infiltration, and attenuated splenic Th1 polarization. Mechanistically, ALX-5407 inhibited MAPK signaling but activated the PI3K-AKT-mTOR pathway, which rapamycin counteracted to amplify suppression.ConclusionsGlyT1 serves as a metabolic checkpoint in Th1 differentiation, and its inhibition by ALX-5407 attenuates allograft rejection through dual suppression of Th1 function and apoptosis induction. Synergy with rapamycin highlights a novel combinatorial strategy to mitigate rejection with reduced toxicity. These findings position GlyT1 targeting as a promising approach for clinical translation in transplantation immunotherapy.